Loop formation by an aortic occlusion balloon catheter during resuscitative endovascular balloon occlusion of the aorta (REBOA) - Yasuyuki Onishi, MD; Hiroyuki Kimura, MD, PhD; Mitsunori Kanagaki, MD, PhD; Shojiro Oka, MD; Genki Fukumoto, MD; Tomoaki Otani, MD; Naoko Matsubara, MD; Kazuna Kawabata, MD, PhD; Masaru Matsumoto, MD; Takao Suzuki, MD, PhD (Radiology Case Reports, 2019)
A 77-year-old man was transferred to our hospital for endoscopically uncontrollable active bleeding from a duodenal ulcer. Soon after his arrival, he became hemodynamically unstable and resuscitative endovascular balloon occlusion of the aorta was performed using a 7-F aortic occlusion balloon catheter (Rescue Balloon; Tokai Medical Products, Aichi, Japan). He became hemodynamically stable and was transferred to the CT room. CT demonstrated that the distal part of the catheter shaft had made a loop in the aorta and the balloon was located at the level of the upper abdomen. We consider the low-profile occlusion balloon catheter to be less rigid than large ones, and care should be taken to prevent balloon migration and catheter shaft bending. Keywords: Resuscitative endovascular balloon occlusion of the aorta, Aortic occlusion balloon catheter